RNAi-mediated Gene Silencing of Mutant Myotilin Improves Myopathy in LGMD1A Mice - Jian Liu; Lindsay M Wallace; Sara E Garwick-Coppens; Darcée D Sloboda; Carol S Davis; Chady H Hakim; Michael A Hauser; Susan V Brooks; Jerry R Mendell; Scott Q Harper (Elsevier, 2014)
Recent progress suggests gene therapy may one day be an option for treating some forms of limb girdle muscular dystrophy (LGMD). Nevertheless, approaches targeting LGMD have so far focused on gene replacement strategies for recessive forms of the disease. In contrast, no attempts have been made to develop molecular therapies for any of the eight dominantly inherited forms of LGMD. Importantly, the emergence of RNA interference (RNAi) therapeutics in the last decade provided new tools to combat dominantly inherited LGMDs with molecular therapy. In this study, we describe the first RNAi-based, preclinical gene therapy approach for silencing a gene associated with dominant LGMD. To do this, we developed adeno-associated viral vectors (AAV6) carrying designed therapeutic microRNAs targeting mutant myotilin (MYOT), which is the underlying cause of LGMD type 1A (LGMD1A). Our best MYOT-targeted microRNA vector (called miMYOT) significantly reduced mutant myotilin mRNA and soluble protein expression in muscles of LGMD1A mice (the TgT57I model) both 3 and 9 months after delivery, demonstrating short- and long-term silencing effects. This MYOT gene silencing subsequently decreased deposition of MYOT-seeded intramuscular protein aggregates, which is the hallmark feature of LGMD1A. Histological improvements were accompanied by significant functional correction, as miMYOT-treated animals showed increased muscle weight and improved specific force in the gastrocnemius, which is one of the most severely affected muscles in TgT57I mice and patients with dominant myotilin mutations. These promising results in a preclinical model of LGMD1A support the further development of RNAi-based molecular therapy as a prospective treatment for LGMD1A. Furthermore, this study sets a foundation that may be refined and adapted to treat other dominant LGMD and related disorders.